Courageous confrontations : lives transformed by life-threatening illness - Helfant, Richard H. (Sentient Publications, 2005)
"Life-threatening illness is more than a crisis of the body; it is a crisis of the soul. During thirty-five as a hospital-based cardiologist, Dr. Helfant often saw patients faced with a catastrophic illness react either with paralyzing fear or great courage. Through his patients' stories, he shows how the critically ill have an opportunity to heal their soul as well as their body. Those who challenge their illness head on frequently awaken to deep internal truths about themselves and emerge with a heightened self-awareness." "Why are some people able to overcome fear and summon their inner strength to find the will to live? By reading their stories of illness and recovery, you will come to understand how a Mafia kingpin, a Wall Street wheeler-dealer, and an arrogant surgeon were able to tap previously hidden resources to confront their mortality."--BOOK JACKET.